The Use of Classroom Languages in Teaching English - Sumarni, Baiq; Firman, Edi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The introduction of English from the beginning is based on a pedagogical concept that the earlier a person is introduced to the target language, the faster and better the child's mastery and acquisition of the language being learned. But unfortunately, the policy of teaching English as a local content subject has not been accompanied by maximum effort from the school. Both in the form of knowledge and teaching skills as well as teacher education qualifications. This condition certainly affects the quality of learning carried out. This study is aimed to describe the use of classroom languages in teaching English used by English teacher in MI Al-Amin Pejeruk, Mataram city. In this research, the writers use descriptive qualitative method. The techniques of data collection in this study are observation, interview, and documentation. The writers use data reduction, data display and data conclusion to analyze the data. The finding shows that the use of classroom languages became one of the effective strategy in teaching English. Through relevant classroom language, children can work together and communicate in learning.